Global research trends and focus on the link between rheumatoid arthritis and neutrophil extracellular traps: a bibliometric analysis from 1985 to 2023 - Chang, Yonglong; Ou, Qinling; Zhou, Xuhui; Nie, Kechao; Liu, Jinhui; Zhang, Sifang (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is an autoimmune disease that currently has an unknown cause and pathogenesis, and is associated with many complications and a high disability rate. The neutrophil extracellular trap network (NETs) is a newly discovered mechanism that allows neutrophils to capture and kill pathogens. Multiple studies in recent years have highlighted its relevance to the progression of rheumatoid arthritis. Despite the growing number of studies indicating the crucial role of NETs in RA, there has been no bibliometric review of research hotspots and trends in this area. In this study, we retrieved articles related to NETs in RA from the Web of Science Core Collection (WoSCC) database from 1985 to 2023 and used visualization tools such as Citespace, VOSviewer, Tableau Public, and Microsoft Office Excel 2021 to analyze the data. After screening, we included a total of 416 publications involving 2,334 researchers from 1,357 institutions in 167 countries/regions, with relevant articles published in 219 journals. The U.S., China, and Germany are the top 3 countries/regions with 124, 57, and 37 publications respectively. Mariana J. Kaplan is the most published author, and journals such as Frontiers in Immunology and International Journal of Molecular Sciences have had a significant impact on research in this field. The clinical application of PAD enzymes and their inhibitors, and the drug development of NETs as therapeutic targets for RA is a trend for future research. Our study provides a comprehensive bibliometric analysis and summary of NETs in RA publications, which will aid researchers in conducting further scientific research.